2019
DOI: 10.1111/tbj.13381
|View full text |Cite
|
Sign up to set email alerts
|

Axillary pseudoaneurysm post core needle biopsy

Abstract: Imaging‐guided Core Needle Biopsy (CNB) is a procedure for tissue sampling in case of suspicious findings, such as breast masses and abnormal lymph nodes. It provides definitive diagnosis with a high accuracy rate and generally with no significant complications. To our knowledge, this is the first case report to document a pseudoaneurysm of the axilla after CNB. An illustrative case and a diagnostic and therapeutic literature review are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…In fact, after conducting a literature search in PubMed using the following search equation "Breast Pseudoaneurysm AND Core Needle Biopsy AND Case Report", only 17 case reports were found (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] P u b l i c a c i ó n a n t i c i p a d a . R e v .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, after conducting a literature search in PubMed using the following search equation "Breast Pseudoaneurysm AND Core Needle Biopsy AND Case Report", only 17 case reports were found (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] P u b l i c a c i ó n a n t i c i p a d a . R e v .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the 17 case reports of breast PA following CNB found in PubMed, it was found that the patients' mean age was 51 years, that Doppler US was mostly used to confirm the PA diagnosis, and that surgical resection and US-guided compression were the main treatments used. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Despite the rarity of breast PA as a complication of CNB, the appearance of large hematomas on the breast following CNB should raise the clinical suspicion of this entity. When this happens, at least a Doppler US should be performed after the resolution of the hematoma.…”
Section: 0mentioning
confidence: 99%
“…1 CTA can be an additional diagnostic imaging modality that allows better detection of origin of the lesion and its relationship with the surrounding structures. 5 CTA is especially useful for planning endovascular treatment of pseudoaneurysms. It is also helpful in the diagnosis of acute arterial bleeding from a ruptured pseudoaneurysm, which manifests as arterial contrast extravasation that persists on a more delayed scan.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-cm pseudoaneurysm that was found on ultrasonograms and computed tomography angiograms (CTA) was surgically resected. 5 Here, we describe a case of an iatrogenic axillary pseudoaneurysm developed after an ultrasoundguided, vacuum-assisted biopsy of the axillary lymph node. The pseudoaneurysm was initially treated with endovascular coil embolization and direct thrombin injection but ultimately required surgical resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Breast pseudoaneurysm: two case reports

Olivares-Antúnez,
Dávila-Zablah,
Garza-Montemayor
2024
MOJCR